2016
DOI: 10.1177/1087054715623046
|View full text |Cite
|
Sign up to set email alerts
|

First-Year GPA and Academic Service Use Among College Students With and Without ADHD

Abstract: Objective: ADHD is a chronic neurodevelopmental disorder that typically results in persistent academic difficulties over time. Although most colleges offer support services, students often do not use the available services or those to which they are entitled. The present study examined predictors of academic performance among college students with and without ADHD. In addition, the rate, predictors, and outcomes of academic service use were explored. Methods: A series of multivariate analyses of variance (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 38 publications
(52 reference statements)
2
29
0
Order By: Relevance
“…Emerging research shows that despite increases in the number of students with ADHD attending university, fewer will attend and graduate 4-year programs than their peers (Kuriyan et al, 2013). Furthermore, undergraduate students with ADHD typically have lower grade point averages (GPAs), increased likelihood of being on academic probation, higher disengagement, poorer academic adjustment, and higher rates of dropout (DuPaul, Pinho, Pollack, Gormley, & Laracy, 2017; Gormley, DuPaul, Weyandt, & Anastopoulos, 2019; Mochrie, Whited, Cellucci, Freeman, & Corson, 2020; Norwalk et al, 2009; Weyandt & DuPaul, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging research shows that despite increases in the number of students with ADHD attending university, fewer will attend and graduate 4-year programs than their peers (Kuriyan et al, 2013). Furthermore, undergraduate students with ADHD typically have lower grade point averages (GPAs), increased likelihood of being on academic probation, higher disengagement, poorer academic adjustment, and higher rates of dropout (DuPaul, Pinho, Pollack, Gormley, & Laracy, 2017; Gormley, DuPaul, Weyandt, & Anastopoulos, 2019; Mochrie, Whited, Cellucci, Freeman, & Corson, 2020; Norwalk et al, 2009; Weyandt & DuPaul, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Given that college students with ADHD achieved a level of success during high school that made postsecondary admission possible, one might reasonably expect that they would continue to experience educational success during college. Contrary to this expectation, research has shown that, relative to their peers, college students with ADHD display significant academic deficits, including lower end-of-semester grade point averages (GPAs), lower levels of performance on weekly assignments and exams, and less effective study strategies (Advokat, Lane, & Lou, 2011; Gormley, DuPaul, Weyandt, & Anastopoulos, 2019; Reaser, Prevatt, Petscher, & Proctor, 2007; Weyandt et al, 2013). Students with ADHD also experience greater difficulties in their general adjustment to college and are at significantly increased risk for displaying comorbid psychiatric disorders, particularly depression and anxiety (Anastopoulos et al, 2018; Blase et al, 2009; Heiligenstein & Keeling, 1995).…”
mentioning
confidence: 99%
“…The body of knowledge about the functioning and manifestation of symptoms in college students and the role that EF plays in this is increasing [ 16 ]. College students with ADHD, compared to students without ADHD, have lower achievement/grade point averages (GPA) [ 17 , 18 , 19 ], and this link between ADHD and low GPA was fully mediated by weak study skills, as measured with the Learning and Study Strategies Inventory (LASSI), a self-report measure assessing strategic learning [ 20 ]. Additionally, college students with ADHD withdraw from more classes than their peers without ADHD [ 17 ].…”
Section: Introductionmentioning
confidence: 99%